Anticoagulation control with the point-of-care INR: A retrospective pre-/post-analysis. Issue 196 (December 2020) - Riva, Nicoletta; Meli, Stephanie; Borg Xuereb, Christian; Vella, Kevin; Ageno, Walter; Makris, Michael; Gatt, Alex
Highlights: Point-of-care (POC) international normalized ratio (INR) testing provides immediate results. It is still debated whether POC-INR monitoring can improve the time in therapeutic range (TTR). We evaluated the TTR from 471 warfarin patients in three timeframes (pre-POC, initial-POC, steady-state-POC). Compared to laboratory-INR, POC-INR monitoring increased the TTR both in the short- and long-term.